A Highly Selective Reaction‐Based Two‐Photon Probe for Copper(I) in Aqueous Media. Issue 8 (11th June 2013) - Maity, Debabrata; Sarkar, Bidyut; Maiti, Sudipta; Govindaraju, T.
<x xml:space="preserve">Abstract</x> Out of the blue: A reaction‐based two‐photon probe XanCu (see scheme) is reported for the selective detection of Cu+ in reducing aqueous environments. Copper(I)‐mediated oxidative benzylic ether (CO) bond cleavage offers "switch‐on" detection of the metal ion.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>